Interfacial electron transfer for carbon dioxide valorization in hybrid inorganic-microbial systems. (15th June 2021) - Pan, Qin; Tian, Xiaochun; Li, Junpeng; Wu, Xuee; Zhao, Feng
Highlights: Interfacial electron transfer is specified in hybrid inorganic-microbial systems. The electron transfer mechanism is key in the energy efficiency of CO2 valorization. The roles of inorganic catalysts and microbes in CO2 reduction are addressed. The application of electricity and solar energy is summarized in a hybrid system. Abstract: Converting carbon dioxide to value-added products with microbial electro- or photosynthesis has attracted significant interest in recent years for relieving global warming effects of fossil fuel use. Hybrid inorganic-microbial systems have been developed to improve the efficiency and selectivity from electricity/solar energy of CO2 conversion. Microbes can acquire electrons from solid donors such as electrode or photosensitizers, understanding the electron transfer mechanisms between inorganic catalysts and microbes is important for designing hybrid systems. However, few reviews have comprehensively summarized the electron transfer mechanisms of hybrid inorganic-microbial interfaces. In this critical review, we classify the electron transfer mechanism of CO2 reduction in hybrid inorganic-microbial systems into direct and indirect pathways. For direct electron transfer, when inorganic catalysts locate on the surface of a cell, electrons transfer from cathode or/and catalysts to the cell via proteins, this process is extracellular electron transfer; when inorganic catalysts are coupled with microbes intracellularly, electrons generate inside the cell and then transfer directly to metabolic pathways, this process is intracellular electron transfer. For indirect electron transfer, the basis of classification is whether redox electron mediators or reductive intermediate products can transfer electrons from inorganic catalysts to microbes. Moreover, the roles of inorganic catalysts and microbes are illustrated in detail to improve the CO2 conversion effectivity and selectivity. Based on this review, the interactions between various inorganic materials and microbes can be understood more clearly, and future research on the reduction of CO2 could be put forward.